2021
DOI: 10.1177/03611981211007143
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Highway Slope using Recycled Plastic Pins

Abstract: The recycled plastic pin (RPP) is made from recycled plastics and waste materials (i.e., polymer, sawdust, fly ash, etc.). It is a lightweight material and is less susceptible to chemical and biological degradation than the alternative reinforcing element. RPPs are driven into the slope face and provide additional resistance along the slip surface which increases the factor of safety against shallow slope failure. The current paper summarizes a case study using RPPs to repair highway slopes, investigating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…The effectiveness of geogrids made from recycled plastic for slope stabilization is well documented through various experimental investigations [ 19 , 20 , 21 , 22 , 23 ]. In fact, many studies have demonstrated that recycled plastics used in geogrids maintain mechanical properties and performance comparable to virgin plastics [ 24 , 25 ]. This is essential, as it ensures that the structural integrity and functionality of the geogrids are not compromised, despite using recycled materials.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of geogrids made from recycled plastic for slope stabilization is well documented through various experimental investigations [ 19 , 20 , 21 , 22 , 23 ]. In fact, many studies have demonstrated that recycled plastics used in geogrids maintain mechanical properties and performance comparable to virgin plastics [ 24 , 25 ]. This is essential, as it ensures that the structural integrity and functionality of the geogrids are not compromised, despite using recycled materials.…”
Section: Introductionmentioning
confidence: 99%